Pengaruh Sikap Mandiri, Motivasi, Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha (Studi Kasus pada Mahasiswa FEB UKSW Konsentrasi Kewirausahaan) - Josia Sanchaya Hendrawan; Hani Sirine (Asian Journal of Innovation and Entrepreneurship, 2017)
The presence and role of the entrepreneur can have an impact on the improvement of economic conditions and the progress of a country. For that, students of Economics and Business Faculty in UKSW who concentrate entrepreneurship are directed to join various entrepreneurship programs in order to foster entrepreneurship interest among students. The purpose of this study is to examine the effect of independent attitudes, motivation, entrepreneurship knowledge on entrepreneurship interests of students on entrepreneurship concentration. The sample of this research is saturated sample, that is population amount equal to number of sample. Respondents are students of entrepreneurship concentration amounting 33 people from 2010-2013. The results of this study indicate that the independent attitude and motivation variables do not affect entrepreneurship interest, while the entrepreneurial knowledge variables affect student entrepreneur interest.